CENTERED PERSON APPLICATION TO IMPROVE STUDENT’S INTERPERSONAL COMMUNICATION SKILLS - Rahmawan, Trisniasari; Subiyanto, Subiyanto; Indiati, Indiati (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2015)
This study aims to determine the application of Person Centered can improve interpersonal communication students in class VIII SMP Negeri 13 Magelang City.The method used in this study is action research guidance and counseling using a cycle consisting of: (1) planning the action, (2) the implementing measures, (3) observation / observation and reflection, (4) evaluation. The data collection techniques used interviews and observations, to determine changes increase interpersonal communication skills in class VIII SMP Negeri 13 Magelang.The results of this study showed the improvement students interpersonal communication skills after three cycles treatments. At the end of cycles, student interpersonal communication skills increase until 83%. It can be concluded that the Person Centered approach can be applied to improve communication skills Interpersonal class VIII SMP Negeri 13 G in Magelang City School.